Predictive Maintenance And Dynamic Control For Enhanced Power ‎Quality In Microgrids (Journal of University of Babylon for Engineering Sciences, 2025)
Microgrids improve economic benefits and environmental sustainability by utilizing distributed generation (DG) from renewable sources like wind and solar. However, there are technological difficulties in integrating these technologies, especially when it comes to energy quality and voltage regulation. Careful management is necessary to address problems including voltage instability, inverter harmonics, and frequency oscillations brought on by low inertia in renewable DG systems. Stable operation can be ensured by addressing these issues with advanced technologies like as FACTS devices, harmonic filters, and Dynamic Voltage Restorer (DVR). Despite the unpredictability of renewable energy sources, real-world case studies from California, Denmark, and India demonstrate how well these solutions work to ensure voltage and frequency stability. Furthermore, energy storage systems (ESS) like supercapacitors and batteries play a critical role in stabilizing voltage and frequency, ensuring reliable microgrid performance.